Antibodies against Receptor Binding Domain of SARS-CoV-2 spike protein induced by BNT162b2 vaccine: results from a pragmatic, real-life study - Marcello Mariani; Maura Acquila; Gino Tripodi; Raffaele Spiazzi; Elio Castagnola (Elsevier, 2021)
Background: As part of the fight against SARS CoV2 infection, vaccination program for health workers at Giannina Gaslini pediatric hospital (IGG) in Genoa, Italy, started on December 2020. We evaluated the anti-Spike protein response in healthcare workers after a complete vaccination scheme of 2 doses spaced by 3 weeks. Methods: Immunoglobulin class G (IgG) against SARS-CoV-2 spike RBD were detected by means of a chemiluminescence immunoassay for quantitative IgG antibodies using Maglumi SARS-CoV-2-S-RBD IgG kit during the 3rd week after vaccination completion. Results: IgG anti SARS-CoV-2 spike protein were detected in 99.88% of 1765 healthcare workers 3 weeks after 2nd dose of BNT162b2. Higher median IgG values were observed in younger subjects (807 UA/mL in under 30 vs 429 UA/mL in over 60; p < 0.001) and those with previous COVID-19 (1284 vs 574 UA/mL; p < 0.001). Conclusion: BNT162b2 is effective in inducing anti SARS-CoV-2 antibodies even in real-life setting. The higher antibody title observed in workers with a previous documented SARS CoV2 infection confirms the possibility to carry out only one dose of BNT162b2 in a context of vaccines shortage.